Pengaruh Disiplin Kerja dan Kepemimpinan Terhadap Kinerja Karyawan Pada PT. Pustaka Rizki Putra Semarang - Meta K. D., Nandha; Prihatini, Apriatni Endang; Listyorini, Sari (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2012)
Work discipline and leadership are factors supporting factor for achieving good performance. PT. Pustaka Rizki Putra Semarang is a company engaged in printing, always providing the best in order to compete. Therefore, it is need of human resources with good performance. In the course of its business activities can not be separated from the problem pinangkatan employee performance by increasing work discipline and leadership. The purpose of this study was to determine the effect of work discipline and leadership on employee performance. Type of research is explanatory. In the study population there were 30 people and all samples used by census. Techniques of data collection using questionnaires, interviews, literature study. Data analysis method used is correlation, simple linear regression and multiple linear regression. The conclusion of this research is the discipline of work and leadership at PT. Pustaka Rizki Putra Semarang is good. Test results with SPSS shows that discipline and leadership have a significant impact on employee performance either simultaneously or partially. Suggestions can be submitted is working discipline should be more attention to the company should be increased. The conclusion of this study is compensation, work environment, workload and leadership on the Main PT Windika quite good. SPSS test result shows that the compensation, work environment, workload and leadership significantly influence job satisfaction either simultaneously or partially. The suggestion that the company should be given more attention is the level of employee discipline. For example, by giving rewards both tangible and intangible for employees to improve disciplin.